Pest categorisation of Cephalcia lariciphila. (19th December 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; et al.
Abstract: The Panel on Plant health performed a pest categorisation of the larch web‐spinning sawfly Cephalcia lariciphila (Hymenoptera: Pamphiliidae) for the EU. The insect has been reported in 11 EU Member States (MSs). It is a quarantine pest listed in Annex IIB of Council Directive 2000/29/EC. Protected zones are in place in Ireland and the UK (Northern Ireland, Isle of Man and Jersey). C. lariciphila can feed on all species of the genus Larix . There have been reported outbreaks in the Czech Republic, Germany, the Netherlands and the UK (England and Wales) in plantations of European larch ( Larix decidua ) and Japanese larch ( Larix kaempferi = Larix leptolepis ). C. lariciphila is absent in the protected zones. The pest can enter the protected zones by human‐assisted spread or by natural spread from EU areas where the pest is present. Plants for planting are considered the most important pathway for the pest. The pest can establish in the protected zones because the climatic conditions are similar to those of the 11 MSs where C. lariciphila is established, and the pest's main host plants are present. The prepupae overwinter in the litter, the adults emerge during May–June, and each female lays 30–40 eggs in slits in mature needles. The larvae feed on the needles through four instars. There is one generation per year; some of the prepupae undergo prolonged diapause for more than 1 year. The impact where the pest occurs is mainly related to the loss of tree growth following defoliation, while tree mortality was locally observed only after repeated defoliation. However, impact is likely to be mitigated by local biological control agents. All criteria assessed by EFSA above for consideration as a potential protected zone quarantine pest and as a potential regulated non‐quarantine pest were met.